The Implementation of the Askisi-SD Neuropsychological Web-Based Screener: A Battery of Tasks for Screening Cognitive and Spelling Deficits of Children - Nikolaos C. Zygouris; Eugenia I. Toki; Filippos Vlachos; Stefanos K. Styliaras; Nikos Tziritas (Education Sciences)
The Askisi-Spelling Deficits (SD) neuropsychological web-based screener was developed to assess cognitive and spelling abilities in children, with an emphasis on the early detection of spelling disorders. This tool incorporates six tasks that evaluate cognitive domains, such as visual and auditory working memory, response inhibition, and spelling processing, providing a comprehensive framework for assessment. A study conducted with 264 Greek children, including 132 children with spelling deficits and 132 typically developing controls, aimed to implement this screening tool. Results indicated that the screener was effective, as children with spelling deficits showed significantly lower performance and longer response times across all tasks. The tool’s internal consistency was supported by split-half correlations (r = 0.64) and Spearman–Brown coefficients (r = 0.78). Nonetheless, certain limitations were identified, including the absence of latency data for specific tasks (Go/No-Go and working memory), as well as the screener’s cultural specificity, which might limit its applicability to other linguistic and orthographic systems. Future iterations should prioritize the inclusion of timing mechanisms for more detailed assessments and consider adaptations for use in languages with varying orthographic complexities. Expanding the demographic reach and conducting longitudinal validation studies would further improve its utility and generalizability. The web-based nature of the screener enables scalable and standardized administration, making it a practical and efficient tool for the early identification of spelling difficulties in children.